Pengaruh Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Hypermart Paragon Semarang (Studi Kasus pada Konsumen Hypermart Paragon Semarang) - Ganang Wahyu Septianto; Agus Hermani DS (Jurnal Ilmu Administrasi Bisnis, 2018)
Rapid economic growth in Semarang creates intense business competition, including retail business. This makes businessman have to work hard to compete in increasing their sales. One way to increase sales on a reatail is to pay attention to the price and quality of service which offered. Hypermart Paragon is one of the retailers that Semarang people choose, but in 2015-2016 the number of sales decreased. If it is not repaired and resolved, it might likely cause problems for Hypermart Paragon. The purpose of this study is to determine the influence of price and quality of service to purchase decisions on consumers Paragon Hypermart Semarang. This type of research is explanatory research. The sampling technique used accidental sampling method. The number of samples taken as many as 100 respondents. Data were analyzed through validity test, reliability test, crosstab, correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, t test, and F test with the help of IBM SPSS program version 16.0. Based on the analysis results can be concluded there is a positive and significant influence between the price and quality of service to the purchase decision partially or simultaneously. This has been proven through a simple linear regression test with the value of the regression price affecting the purchase decision of 0.422 and the quality of service affect the purchase decision of 0.199. The suggestion for Hypermart Paragon is to pay attention to the price of some items that are more expensive than competitors and to train employees and increase the service support facilities to improve the quality of service in Hypermart Paragon.